Kinerja Reaktor Ohmic Dengan Sistem Kendali Fuzzy Expert: Performance of the Ohmic Reactor with Fuzzy Expert Control System - Ayla Ainayyah M; Abdul Waris; Ahmad Munir (Jurnal Agritechno, 2026)
The heating process is a technique for preserving and processing foodstuffs. One of the methods that can be used is ohmic heating method. Ohmic reactors system today on the less optimal of the ohmic reactor performance so that additional control system is required for the ohmic reactor. The purpose of this research is to produce a fuzzy expert control system in the ohmic reactor to optimalize the performance of the ohmic reactor. This research conducted by creating hardware and software. The test used a salt solution at a concentration of 1%, 2%, 3%, 4% as the test material. Heating is carried out at each solution concentration. The analysis result of the temperature response showed that the fuzzy expert control system in the ohmic reactor is operating well. This can be seen from the overshoot of the solution temperature only at a concentration of 4% of 2 ℃ for 4 seconds while in fuzzy showed an overshoot of 3 ℃ for 2 seconds. In addition, the setting time to reach the setting point was relatively small and the solution temperature was relatively stable. The fuzzy expert and fuzzy control systems have low steady state errors ranging from 1,1% and 2,2%. Meanwhile, the analysis results of the temperature response in the on-off control system do not meet the criteria for the success performance control due to overshoot, unstable solution temperature and large steady state errors in each solution concentrations. The used energy analysis found that the electrical energy used by fuzzy expert control system was 49169,2 Watt.s and fuzzy Sugeno was 45121,5 Watt.s.